2011
DOI: 10.1128/iai.00658-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Microbicidal Effects of Human Histone Proteins H2A and H2B on Leishmania Promastigotes and Amastigotes

Abstract: Recent studies have shown that histone proteins can act as antimicrobial peptides in host defense against extracellular bacteria, fungi, and Leishmania promastigotes. In this study, we used human recombinant histone proteins to further study their leishmaniacidal effects and the underlying mechanisms. We found that the histones H2A and H2B (but not H1(0)) could directly and efficiently kill promastigotes of Leishmania amazonensis, L. major, L. braziliensis, and L. mexicana in a treatment dose-dependent manner.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 56 publications
7
60
0
Order By: Relevance
“…However, we observed that amastigotes are highly resistant to neutrophil microbicidal mechanisms and induce anti-inflammatory IL-10 release, while promastigotes trigger more TNF-␣ secretion and are more susceptible to killing by neutrophils. Collectively, this study supports and expands upon our previous understanding of the role of neutrophils during leishmaniasis (10,22) and highlights the possible cross talk between neutrophils and other immune cells involved in parasite recognition and clearance.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, we observed that amastigotes are highly resistant to neutrophil microbicidal mechanisms and induce anti-inflammatory IL-10 release, while promastigotes trigger more TNF-␣ secretion and are more susceptible to killing by neutrophils. Collectively, this study supports and expands upon our previous understanding of the role of neutrophils during leishmaniasis (10,22) and highlights the possible cross talk between neutrophils and other immune cells involved in parasite recognition and clearance.…”
Section: Discussionsupporting
confidence: 67%
“…However, the immunological ramifications of amastigote-neutrophil interactions remain largely uncharacterized. We have recently demonstrated that L. amazonensis amastigotes are highly resistant to the antimicrobial effects of purified human histone proteins (22), which are known to be released together with other microbicidal agents when neutrophils undergo NETosis (23). Currently, it is unclear whether neutrophils recognize amastigotes and influence amastigote clearance or persistence (24).…”
mentioning
confidence: 99%
“…In an analysis of histone toxicity to L. major, a cutaneous leishmaniasis-causing agent, it was demonstrated that lpg1 Ϫ mutants, which lack LPG, were equally as susceptibility to histone killing as the wild-type promastigotes (48). Also, preincubation of histone with purified L. major LPG reduced the rate of death of wild-type promastigotes without affecting lpg1 Ϫ mutants (48). LPG is highly polymorphic, varying among different Leishmania species and even strains (45).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of LPG in protecting parasites from NET killing mediated by histones associated with these traps is complex and remains to be established. Moreover, Leishmania surface metalloprotease (GP63) seems to participate in promastigote escape from NET histone killing, since it has been shown that knockdown of L. amazonensis GP63 increased parasite susceptibility to histone killing (48).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoneutralization of histones can abrogate killing of the parasites, supporting the antiparasitic activity of histones. In addition, purified H2A and H2B, but not H1, can kill Leishmania promastigotes [33].…”
Section: Antiparasitic Activitymentioning
confidence: 99%